Kajian Perencanaan dan Pengendalian Anggaran Pendapatan Belanja Pada Badan Keuangan Daerah Parepare - Adyaqsha (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2022)
Government agencies are one form of non-profit organizations that aim to improve services to the general public which can be in the form of improving security, improving the quality of education or health quality and others. This research aims to find out the process of Income Budget Planning and spending at the Parepare Regional Finance Agency and the Process of Controlling the Budget of revenue and expenditure at the Parepare Regional Finance Agency. To apply this goal, qualitative methods are used, using observation and interview techniques. The results of this study showed the Budget Planning Process of revenue and expenditure at the Parepare Regional Financial Agency. Planning process based on programs and activities running effectively, The process of controlling revenue and spending budgets carried out at the regional financial agency of Parepare city both monitoring and evaluation.